Repurposing Verapamil to Enhance Killing of T-ALL Cells by the mTOR Inhibitor Everolimus - Micol Silic-Benussi; Evgeniya Sharova; Alberto Corradin; Loredana Urso; Vittoria Raimondi; Ilaria Cavallari; Barbara Buldini; Samuela Francescato; Sonia A. Minuzzo; Donna M. D'Agostino; Vincenzo Ciminale (MDPI AG, 2023)
New therapies are needed for patients with T-cell lymphoblastic leukemia (T-ALL) who do not respond to standard chemotherapy. Our previous studies showed that the mTORC1 inhibitor everolimus increases reactive oxygen species (ROS) levels, decreases the levels of NADPH and glucose-6-phosphate dehydrogenase (G6PD), the rate-limiting enzyme of the pentose phosphate pathway (PPP), and induces apoptosis in T-ALL cells. Studies in T-ALL-xenografted NOD/SCID mice demonstrated that everolimus improved their response to the glucocorticoid (GC) dexamethasone. Here we show that verapamil, a calcium antagonist used in the treatment of supraventricular tachyarrhythmias, enhanced the effects of everolimus on ROS and cell death in T-ALL cell lines. The death-enhancing effect was synergistic and was confirmed in assays on a panel of therapy-resistant patient-derived xenografts (PDX) and primary samples from T-ALL patients. The verapamil-everolimus combination produced a dramatic reduction in the levels of G6PD and induction of p38 MAPK phosphorylation. Studies of NOD/SCID mice inoculated with refractory T-ALL PDX cells demonstrated that the addition of verapamil to everolimus plus dexamethasone significantly reduced tumor growth in vivo. Taken together, our results provide a rationale for repurposing verapamil in association with mTORC inhibitors and GC to treat refractory T-ALL.